Evaluating the Suitability of the Low Energy Availability in Females Questionnaire (LEAF-Q) for Female Football Players - Marcus S. Dasa; Oddgeir Friborg; Morten Kristoffersen; Gunn Pettersen; Jørn V. Sagen; Jorunn Sundgot-Borgen; Jan H. Rosenvinge (SpringerOpen, 2023)
Abstract Background The Low Energy Availability in Females Questionnaire (LEAF-Q) is a screening tool developed to detect endurance athletes and dancers at risk for development of persistent low energy availability (LEA) and the female athlete triad (Triad). This study investigated the applicability of the LEAF-Q in a cohort of sixty professional female football players. Methods The participants were classified as at risk (≥ 8) or not at risk (< 8) for persistent LEA and the Triad according to their LEAF-Q score, before being compared. Receiver operating curves were then conducted to examine the ability of the overall LEAF-Q and subcategories to correctly determine the presence of clinically defined markers of the Triad. Additionally, Youden's index was calculated to determine the best fitting cut-off values. Results Thirty-two percent of participants were classified as at risk by the LEAF-Q. We found no statistically significant differences between the two groups for any markers associated with persistent LEA. Except for acceptable accuracy in determining menstrual status, all other LEAF-Q components exhibited poor accuracy and predictive values. Youden's index scores imply that increasing the overall and injury cut-off values to ≥ 10 and ≥ 5 respectively, would yield increased performance. Conclusions Our findings do not support the use of the LEAF-Q for the purpose of detecting LEA and Triad conditions among female football players.